Detenction and characterization of stone fruit virus diseases in Tunisia - Boulila, Mohamed (Phytopathologia Mediterranea, 2001)
A preliminary survey was conducted in Tunisia to identify stone fruit (almond, plum, peach) virus diseasesoccurring in orchards and mother block stands. Two ilarviruses, Prunus necrotic ringspot virus (PNRSV) andPrune dwarf virus (PDV) infecting almond and plum and a trichovirus, Apple chlorotic leaf spot virus (ACLSV) foundin a peach orchard in northern Tunisia, were detected. These viruses were detected by means of herbaceous andwoody indicators (cucumber, peach GF 305), serology (DAS-ELISA), electron microscopy (DIP, ISEM, Decoration)and reverse transcription-polymerase chain reaction-based assay (RT-PCR). Furthermore, typing PNRSV isolateswas done by bioassays using various species and cultivars of Cucurbitaceae, serotyping with specific monoclonalantibodies (Mabs) in ELISA-DASI and RFLP analysis. Characterization work showed that serotyping with Mabswas the best mean to distinguish between PNRSV isolates.